1912
DOI: 10.5962/bhl.title.44155
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity of caffein: an experimental study on different species of animals

Abstract: About the same time Amory * (1868) published the results of his Studies on the toxicity of caffein in cats, dogs, rabbits, and pigeons. In all cases very large doses were introduced directly into the stomach by means of a temporary gastric fistula. Ten grains given in meat to a dog caused restlessness, but no other symptoms. Doses of 30 grains and above were invariably fatal. Seventy-three grains given to a cat caused death within 20 minutes. From observations on frogs, guinea pigs, rabbits, and on one dog, Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1942
1942
1982
1982

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…From the small number of papers which have been published on the subject, it is probable -that the response of animals to Zn injections will be found to be similar to that of human beings. Salant, Rieger & Treuthardt [1918] injected Zn into rabbits and cats in quantities relatively greater than those used in the present experiments, and subsequently found very little in the urines, but quantities up to half the amounts injected in the intestinal tracts. It is not clear from their paper, however, whether due allowance was made for the Zn in the animals' food, and particularly in that of the rabbits.…”
Section: The Fate Of Injected Znmentioning
confidence: 54%
“…From the small number of papers which have been published on the subject, it is probable -that the response of animals to Zn injections will be found to be similar to that of human beings. Salant, Rieger & Treuthardt [1918] injected Zn into rabbits and cats in quantities relatively greater than those used in the present experiments, and subsequently found very little in the urines, but quantities up to half the amounts injected in the intestinal tracts. It is not clear from their paper, however, whether due allowance was made for the Zn in the animals' food, and particularly in that of the rabbits.…”
Section: The Fate Of Injected Znmentioning
confidence: 54%
“…In recent years the toxicity of tin has aroused little interest, but in the latter part of the last century and the first decade of this, considerable attention was paid to the possible contamination of food preserved in cans (White, 1881;Ungar and Bodlander, 1886; Lehmann, 1902;Eckhardt, 1909;Schryver, 1909). It was concluded that there was no serious risk; since then there have only been occasional studies on the toxicity of tin compounds (Salant, Rieger, and Trenthardt, 1914;Handovsky, 1925;Schwartzer and Clarke, 1927;Seifter and Rambousek, 1943). A suggestion that the fungicidal properties of certain organic tin compounds might have industrial application (Van der Kerk and Luijten, 1954) coupled with their use as " plasticizers " has rekindled interest in this subject.…”
mentioning
confidence: 99%